Premorbid cognitive deficits in young relatives of schizophrenia patients - Keshavan, Matcheri S.; Kulkarni, Shreedhar R.; Bhojraj, Tejas; Francis, Alan; Diwadkar, Vaibhav; Montrose, Debra M.; Seidman, Larry; Sweeney, John (Frontiers in Human Neuroscience, 2010)
Neurocognitive deficits in schizophrenia are thought to be stable trait markers that predate the illness and manifest in relatives of patients. Adolescence is the age of maximum vulnerability to the onset of schizophrenia and may be an opportune “window” to observe neurocognitive impairments close to but prior to the onset of psychosis. We reviewed the extant studies assessing neurocognitive deficits in young relatives at high risk (HR) for schizophrenia and their relation to brain structural alterations. We also provide some additional data pertaining to the relation of these deficits to psychopathology and brain structural alterations from the Pittsburgh Risk Evaluation Program (PREP). Cognitive deficits are noted in the HR population, which are more severe in first-degree relatives compared to second-degree relatives and primarily involve psychomotor speed, memory, attention, reasoning, and social-cognition. Reduced general intelligence is also noted, although its relationship to these specific domains is underexplored. Premorbid cognitive deficits may be related to brain structural and functional abnormalities, underlining the neurobiological basis of this illness. Cognitive impairments might predict later emergence of psychopathology in at-risk subjects and may be targets of early remediation and preventive strategies. Although evidence for neurocognitive deficits in young relatives abounds, further studies on their structural underpinnings and on their candidate status as endophenotypes are needed.